2021
DOI: 10.1530/ec-21-0146
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves glycemic variability in adults with type 1 diabetes mellitus: an open-label randomized control trial

Abstract: Introduction: Metformin has been demonstrated to enhance cardioprotective benefits in type 1 diabetes (T1DM). Although glycemic variability (GV) is associated with increased risk of CVD in diabetes, there is a scarcity of research evaluating the effect of metformin on GV in T1DM. Objectives: In the present study, the effects of adjuvant metformin therapy on GV and metabolic control in T1DM were explored. Patients and methods: A total of 65 adults with T1DM were enrolled and subjected to physical examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…In a recent study of metformin effect on GV, the MAGE (primary outcome), standard deviation of blood glucose, largest amplitude of glycaemic excursions and CV demonstrated significant improvement in metformin group; patients with higher BMI presented greater reduction in MAGE and %CV. 26 In our study which involved overweight/obese patients, significant reduction in %CV was observed but not MAGE. Another study did not find any significant variation in GV.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In a recent study of metformin effect on GV, the MAGE (primary outcome), standard deviation of blood glucose, largest amplitude of glycaemic excursions and CV demonstrated significant improvement in metformin group; patients with higher BMI presented greater reduction in MAGE and %CV. 26 In our study which involved overweight/obese patients, significant reduction in %CV was observed but not MAGE. Another study did not find any significant variation in GV.…”
Section: Discussionmentioning
confidence: 44%
“…However, our results were almost similar to a recent study, which reported 23.5% of adverse event in MET group. 26 Metformin is generally well-tolerated. This is a carefully designed and well-conducted clinical study to explore the effects of adjunct metformin treatment on GV in overweight/obese adults with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…The same study reported improvements in levels of proatherogenic lipid profiles, irrespective of previous background statin therapy [91]. Evidence from a small randomized-controlled study also suggests fewer glycemic fluctuations in metformin users with T1D [92].…”
Section: Metforminmentioning
confidence: 85%
“…All the patients were provided with the same dietary and physical activity guidance by the same dietician and diabetes educator before being randomly assigned a group. 12 …”
Section: Methodsmentioning
confidence: 99%